2018
DOI: 10.1186/s12978-018-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting modern contraceptive use among fecund young women in Bangladesh: does couples’ joint participation in household decision making matter?

Abstract: ObjectivesThe purpose of the study was to explore the association between couples’ joint participation in household decision making and modern contraceptive use (MCU) among fecund (physically able to bear child) young women in Bangladesh.MethodsThis study utilized a cross-sectional data (n = 3507) extracted from the Bangladesh Demographic and Health Survey (BDHS) 2011. Differences in the utilization of modern contraceptives (MC) by socio-demographic characteristics were assessed by χ2 analyses. Binary logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 32 publications
9
62
1
4
Order By: Relevance
“…This study also revealed geographical region where a woman lived was found to be an important predictor of modern contraceptive utilization. This supported by study done in Malawi (36), Bangladesh (37) and Uganda(7). This might be due to the fact that attributable to the tendency of some region to have higher fertility compared to others .Additional reason may be family planning services ,cultural and religious reason (55).…”
Section: Geographical Variation and Clustering Of Modern Contraceptivsupporting
confidence: 60%
See 1 more Smart Citation
“…This study also revealed geographical region where a woman lived was found to be an important predictor of modern contraceptive utilization. This supported by study done in Malawi (36), Bangladesh (37) and Uganda(7). This might be due to the fact that attributable to the tendency of some region to have higher fertility compared to others .Additional reason may be family planning services ,cultural and religious reason (55).…”
Section: Geographical Variation and Clustering Of Modern Contraceptivsupporting
confidence: 60%
“…It was higher than study done in Malawi (36). But it was low when compared to study done in Bangladesh (37), Ghana (5). The possible explanation for this variation might be due to the involvement of health extension workers in awareness creation activity, difference in provision of health service including in school through different club related to reproductive health programmers, availability of youth friendly health service or difference of study population (38)(39)(40).…”
Section: Discussionmentioning
confidence: 68%
“…In Nigeria, the Maternal Mortality Ratio (MMR) is still on the high side of 576 per 100,000 live births 3 . Evidences has shown that obstetric deaths could be reduced by 20 percent through the correct adoption of family planning (FP) 4,5 , statistics also showed that an increase of 15 to 17 percent of contraceptives utilization decreases population growth by one birth per woman 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Family planning (FP) low utilization is one of the signi cant issues in many developing countries with poor access to maternal and child health care services. 6,7 There is an unmet need for family planning among estimated 215 million women in these countries and 82 percent of unintended pregnancies could be a could be attributed to the FP unmet need. 9 Inaccessibility to effective FP is particularly high in the postpartum period 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation